The Holy See and its role in the international system A study in the soft power of the religious actor in international relations - salloum, Assistant Prof Dr saad (The International and Political Journal, 2023)
The study analyzes the role of the Holy See in the international system, by analyzing the soft power of the religious actor in international relations, and the unconventional nature of the diplomacy of the Holy See based on the intertwining of the religious and the political. The study reviews the most prominent examples of the role of the Holy See in international crises, since the adoption of the policy of external openness to all world powers after the Second Vatican Council (1962-1965), and the attempt to reduce historical differences with some countries such as China and the Soviet Union, and move away from Western and American preferences with regard to Russia, and the use of the Holy See’s privileged position in the United Nations to influence a wide range of global issues, His mediation of conflict between a variety of nations reveals impressive possibilities for the use of faith-based diplomacy.